Impact of the economic crisis on foreign direct investment in Serbia - Zlatković, Miodrag; Kostić, Zorana (Hotel and Tourism Management, 2014)
The consequences of the economic crisis caused macroeconomic instability. The economic system of Serbia is not resistant to exogenous disturbances and absorbs the negative effects that come from the global environment. The consequences of the crisis directly affected the inflow of foreign direct investments, and indirectly caused distortions in the labor market and living standard of the population. One of the challenges faced by countries in transition such as Serbia is how to increase the investment amount and improve its structure. The aim of this paper is to review trends in foreign direct investments in Serbia in the past period. We use analytical processing to give an overview of achieved macroeconomic results in the economic reality of the Serbian economy after the wave of crisis. Effects of the crisis will affect the creation of an adequate environment for attracting investors.